The Effect of Interpersonal Communication of Tax Service Officers on the Perception and Level of Taxpayer Satisfaction at KPP Pratama Lubuk Pakam - Febby Christie Br. Ginting; Suwardi Lubis; Sakhyan Asmara (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to analyze the effect of interpersonal communication of tax service officers on the perception and level of satisfaction of taxpayers at KPP Pratama Lubuk Pakam. The theory used in this study is the theory of interpersonal communication by Devito (2015), the theory of perception by Murtiadi (2015), and the theory of the level of satisfaction of public services according to Berry et al (2011). This study uses a quantitative method that is correlational, with a population of all individual taxpayers who are actively registered at KPP Pratama Lubuk Pakam and a sample of 100 respondents through purposive sampling technique. Data was collected by distributingquestionnaires online through google forms and literature studies. Data analysis was performed using thecorrelation formula Pearson and simple linear regression analysis. The findings of this study indicate that interpersonal communication has a significant effect on the perception of taxpayers by 69%, and on the level of satisfaction of taxpayers by 74.6%. So it can be concluded that the success of the tax service officer's communication is one of the determinants of the taxpayer's own perception of taxes, and will determine the extent to which the taxpayer's level of satisfaction with tax services he gets from tax officials.